Pengaruh Kompetensi dan Kreativitas Montir Terhadap Keunggulan Bersaing pada Pelaku Usaha Bengkel Motor Kec. Cikarang Timur - Dede Wahyudin; Enjang Suherman; Laras Ratu Khalida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research investigates the influence of mechanic competency and creativity on competitive advantage in motorbike repair shops in East Cikarang District. The method of research applies a quantitative descriptive approach. The data collection method in this research is the questionnaire and Likert scale. In this study, the population was 50 motorbike repair shop business actors in East Cikarang. The sampling technique in this study used a saturated sampling technique where all population members became research subjects in data analysis. Multiple linear regression analysis techniques with a significance level of 0.05. Comprehensive analysis calculations using the SPSS version 27 program. The results of the research reveal that (1) partial competence has a significant positive effect on competitive advantage in East Cikarang motorbike repair shop business actors, (2) partial creativity has a significant positive impact on competitive advantage in repair shop business actors motorbikes in East Cikarang District, (3) simultaneously the competency and creativity of mechanics have a significant positive effect on the competitive advantage of motorbike repair shops in East Cikarang District. Motorbike repair business operators must develop the competency and creativity of existing mechanics to increase their competitive advantage.